(untitled) (Studia Prawnicze / The Legal Studies, 1993)
Rozróżnienie ius cogens – ius dispositivum należy do podstawowych rozróżnień pojęciowych aprobowanych w prawoznawstwie. Artykuł objaśnia czym ius cogens różni się od ius dispositivum, ze względu na jakie to właściwości całe ius ulega podziałowi na owe dwa działy czy rodzaje. The ius cogens - ius dispositivum distinction is one of the basic conceptual distinctions acknowledged in legal studies. The article explains how ius cogens differs from ius dispositivum and which properties lead to the division of the ius as a whole into these two parts or types.